The effect of subjective age on loneliness in the old adults: The chain mediating role of resilience and self-esteem - Xie, Jin; Zhang, Bo; Yao, Zhendong; Zhang, Wenya; Wang, Jingli; Zhao, Chun-ni; Huang, Xinquan (Frontiers in Public Health, 2022)
Objectives: This study aimed to explore the effect of subjective age on loneliness in the old adults, and the mediating role of resilience and self-esteem in subjective age and loneliness. Methods: About 450 old adults from Jiangxi、Hunan、Henan province completed The third edition of the Loneliness Scale (UCLA-LS III), Age Decade Scale (ADS), Connor-Davidson Resilience Scale (CD-RISC) and Self-Esteem Scale (SES). Results: (1) Subjective age was significant positively correlated with loneliness. (2) Resilience, self-esteem and loneliness were significant negatively correlated. (3) Subjective age affected loneliness through the mediating effects of resilience and self-esteem, respectively. (4) Resilience and self-esteem played a chain mediating role between subjective age and loneliness. Conclusions: Resilience and self-esteem can directly affect the loneliness of the old adults alone, and can also affect the loneliness of the old adults through the chain mediating effect of resilience and self-esteem.